Antihypertensive and antioxidant activities of enzymatic wheat bran protein hydrolysates. Issue 1 (29th October 2019) - Zou, Zhipeng; Wang, Mingjie; Wang, Zhigao; Aluko, Rotimi E.; He, Rong
Abstract: Bioactive peptides from plant protein sources have been continuously identified as nutrient supplements for low toxicity but multiple physiological activities such as antihypertensive, antioxidant, and anti‐inflammatory. In this study, wheat bran protein isolate was digested with alcalase to produce wheat bran protein hydrolysate (WPH) that was then separated into different peptide fractions (<1, 1–3, 3–5, and 5–10 kDa) by membrane ultrafiltration. WPH and the peptide fractions were evaluated for in vitro activities such as antioxidant, renin inhibition, and angiotensin‐converting enzyme (ACE) inhibition. In addition, the blood pressure‐lowering effects of WPH and the <1 kDa peptides were determined by oral administration to spontaneously hypertensive rats (SHRs). Results showed that the ACE and renin inhibitions were significantly ( p < .05) higher for the <1 kDa fraction (84.25% ± 2.45%, 75.19% ± 1.75%, respectively) when compared to the WPH and >1 kDa fractions. The <1 kDa fraction also showed significantly ( p < .05) higher oxygen radical antioxidant activity with 2044.73 ± 37.45 (μM TE/g protein) when compared to lower values obtained for the >1 kDa membrane fractions and WPH. Oral administration (100 mg/kg body weight) of the <1 kDa membrane fraction to SHRs resulted in a better decrease (−35 mmHg) in the systolic blood pressure when compared to the WPH (−20 mmHg) after 6 hr. And seven peptides (NL, QL, FL, HAL, AAVL, AKTVF, and TPLTR) were identified and amino acid sequence was determined by tandem mass spectrometry. We conclude that the WPH could be considered as a suitable natural antihypertensive and antioxidant resource. Practical applications: The results of the present study indicate that WPH and its ultrafiltration fractions possess potential as a source of antihypertensive and strong antioxidant peptides. It has been proved that wheat bran has a good blood pressure lowering and antioxidation and other biological activities, and the <1 kDa fraction showing high oxygen radical absorbance capacity level also has better in vitro ACE inhibition and renin‐inhibitory activity. The higher antihypertensive efficiency of the <1 kDa fraction may be because the peptides can be better absorbed from the gastrointestinal tract or an increased ability to interact with the enzyme (ACE or renin) protein structure to change the active conformation and lead to decreased catalysis. The results of this study indicate that WPH, especially <1 kDa peptide, can be used as a component in formulating antihypertensive functional foods and nutraceuticals, thus improving the industrial production efficiency and bioavailability of wheat bran.